Understanding of Consumer Behavior Toward Environmental Sustainability on Electric Vehicle Purchase Intentions in Indonesia - Sri Hartono; Mohamad Fazli Sabri; Agustinus Hariadi Djoko Purwanto (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Indonesia is currently facing a significant problem of air pollution caused by vehicle emissions, which severely impacts both health and the economy. With the depletion of natural resources, the cost of gasoline is on the rise. Purpose: To address this issue, a study was conducted to investigate consumer behavior and their awareness of environmental sustainability when purchasing electric vehicles. Design/methodology/approach: A purposive sampling method was used, and the survey was conducted on 140 individuals who own fossil fuel-powered vehicles. The research utilized Smart PLS for data processing. Findings/Result: The results confirmed two hypotheses and refuted two based on prior research.Conclusion: Findings indicate environmental awareness, but barriers to EV adoption persist.Originality/value (State of the art): Adds new evidence on EV purchase decisions in emerging markets. Keywords: environmental concern, attitude, subjective norm, behavior control, electric vehicle purchase intention